The Impact of Mobile Payment Systems and User Interface Design on Customer Adoption and Transaction Volume in E-commerce Companies in Jakarta - Judijanto, Loso; Wardhani, Diky (Eastasouth Institute, 2024)
This study investigates the impact of mobile payment systems and user interface design on customer adoption and transaction volume in e-commerce companies in Jakarta. Utilizing a quantitative approach, data were collected from 140 respondents and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that both mobile payment systems and user interface design significantly and positively influence customer adoption. Additionally, customer adoption was found to have a positive impact on transaction volume. The study highlights the critical role of efficient mobile payment solutions and intuitive user interface designs in enhancing consumer engagement and transaction outcomes. These insights provide valuable guidance for e-commerce businesses in Jakarta, emphasizing the need to optimize technological and design elements to improve competitive advantage and drive business growth.